The Characteristics of Qur'anic Interpretation in Indonesia: A Study of Al-Singkili's Thoughts on The Concept of Education in The Family Based on Suroh Al Luqman 13-17 - Rizayanti, Hana; Husna, Jannatul; Waharjani, Waharjani (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This article aims to examine Tarjuman Al-Mustafid's interpretation of an interpretation by an archipelago cleric named 'Abd al-Rauf bin 'Ali al-Fanshuri al-Jawi. The urgency of the research in this article is to provide a basic description of the character of the interpretation of the characters in the content and content of the Qur'an which then contributed to developing Islamic civilization at that time. Moreover, the focus of this research is a study of Al-Singkili's thoughts regarding Luqman's message which contains Islamic religious education in the family based on Surah Luqman verses 13-17. The concept of Islamic religious education taught in the family refers to Surah Luqman verses 13-17, about the content of Luqman's message which is reflected as a wise and wise figure in educating his children, so that the contents of the message are used as the basis for parents today in educating their children. This research uses a qualitative approach with library research methods. The results of this study indicate that, the education contained in Surah Luqman verses 13-17 according to Al-Singkili's thinking includes: (1) monotheism education, (2) filial education to parents, (3) virtuous charity education, (4) worship education.